2005
DOI: 10.1111/j.1471-4159.2005.03437.x
|View full text |Cite
|
Sign up to set email alerts
|

The galanin‐R2 agonist AR‐M1896 reduces glutamate toxicity in primary neural hippocampal cells

Abstract: Galanin is a neuropeptide involved in a variety of biological functions, including having a strong anticonvulsant activity. To assess a possible role of galanin in modulation of glutamatergic synapses and excitotoxicity, we studied effects of a galanin receptor 2(3) agonist (AR-M1896) on several molecular events induced by glutamate administration in primary neural hippocampal cells. Exposure of cells, after 5 days in vitro, to glutamate 0.5 mM for 10 min caused morphological alterations, including disaggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 72 publications
(77 reference statements)
3
34
1
Order By: Relevance
“…We have preliminary results showing protective effects of galanin against apoptotic cell death induced by the broad kinase inhibitor staurosporine in primary hippocampal neurons (R.T., unpublished data). These data are in agreement with previous results where galanin or GalR2 agonist AR-M1896 promotes survival of hippocampal neurons undergoing exicitotoxic injuries (62,63), by activation of GalR2 and hence Akt and ERK pathway (62). Our present data, showing that galanin causes chromatin condensation, loss of membrane potential, release of cyt c into the cytosol, and activation of caspases only in GalR2 cells as a result of inhibition of PI3K/Akt pathway, enlighten the opposing roles of GalR2 in tumor and nontumor cells.…”
Section: Figsupporting
confidence: 83%
“…We have preliminary results showing protective effects of galanin against apoptotic cell death induced by the broad kinase inhibitor staurosporine in primary hippocampal neurons (R.T., unpublished data). These data are in agreement with previous results where galanin or GalR2 agonist AR-M1896 promotes survival of hippocampal neurons undergoing exicitotoxic injuries (62,63), by activation of GalR2 and hence Akt and ERK pathway (62). Our present data, showing that galanin causes chromatin condensation, loss of membrane potential, release of cyt c into the cytosol, and activation of caspases only in GalR2 cells as a result of inhibition of PI3K/Akt pathway, enlighten the opposing roles of GalR2 in tumor and nontumor cells.…”
Section: Figsupporting
confidence: 83%
“…We have recently extended these findings by demonstrating that organotypic hippocampal cultures from mice with a loss-of-function mutation in GalR2 (GalR2-MUT) treated with glutamate show more cell death than WT controls and this cannot be rescued with the addition of either exogenous galanin or Gal2-11 (16). In support of these findings, studies by Pirondi and colleagues have shown that glutamate induced upregulation of c-fos can be reversed using galanin or Gal2-11 (17). Similarly, in vivo studies using an adeno-associated virus expressing the coding sequence for the galanin peptide reduced kainic acid-induced hippocampal cell death in rats (18), whilst addition of galanin or Gal2-11 in vitro protected basal forebrain cultures from A-beta-induced neurotoxicity (19).…”
supporting
confidence: 66%
“…Several lines of evidence indicate that activation of the GALR2 receptor elicits a neuroprotective signal. The AR-M1896 GALR2 agonist protects both mouse [32] and rat [99] primary neuronal hippocampal cultures from glutamate or staurosporine-induced [32] cell death. More recently, GAL failed to prevent glutamate-induced hippocampal cell death in cultures from GALR2 knockout (GALR2KO) mice [100].…”
Section: Galanin Plasticity As a Neuroprotective Factor In Admentioning
confidence: 99%